2016
DOI: 10.1148/radiol.16142535
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Applications in Mild Traumatic Brain Injury: An Imaging Update

Abstract: Mild traumatic brain injury (mTBI), also commonly referred to as concussion, affects millions of Americans annually. Although computed tomography is the first-line imaging technique for all traumatic brain injury, it is incapable of providing long-term prognostic information in mTBI. In the past decade, the amount of research related to magnetic resonance (MR) imaging of mTBI has grown exponentially, partly due to development of novel analytical methods, which are applied to a variety of MR techniques. Here, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 175 publications
1
44
0
Order By: Relevance
“…The PCSSs were assessed by using self-report questionnaires and were reported in Z-scores, for which higher scores indicated greater symptom. 26…”
Section: Subjectsmentioning
confidence: 99%
“…The PCSSs were assessed by using self-report questionnaires and were reported in Z-scores, for which higher scores indicated greater symptom. 26…”
Section: Subjectsmentioning
confidence: 99%
“…Susceptibility-weighted perfusion MRI may be difficult to obtain in the acute TBI setting secondary to patient contraindications and is limited by signal loss in the presence of blood products, but may be valuable in subacute or chronic TBI particularly when combined with other conventional and advanced MRI techniques including DTI. 4042 Patients with mild TBI and normal conventional imaging have demonstrated perfusion deficits that correlate with neurocognitive impairment. 43,44 TBI causes axonal and capillary disruption 45 that can be observed as WMH on FLAIR MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, its underlying pathophysiological mechanisms of complex posttraumatic symptoms are poorly understood, leading to a paucity of successful treatment strategies . There is usually no evidence of brain structural abnormality on conventional neuroimaging, such as computed tomography (CT) and magnetic resonance imaging (MRI) scans, despite the fact that there are quite a few recently developed advanced neuroimaging techniques including functional (f)MRI for detecting brain abnormalities in MTBI such as thalamic injury and white matter atrophy . The commonly reported sequelae following TBI of any severity include fatigue, problems with sleep, problems with appetite and arousal, and lack of motivation, which are all closely related to hypothalamic dysfunction and neuropeptide dysregulation .…”
mentioning
confidence: 99%
“…Resting‐state functional MRI (RS‐fMRI) has recently drawn more attention in detecting robust various neuronal functional connectivity patterns . Using RS‐fMRI, studies have consistently demonstrated phase‐locked low‐frequency oscillations (<0.1 Hz) of blood oxygenation level‐dependent (BOLD) signal across functionally connected brain regions (resting state networks, RSNs) in the resting brain . There are several well‐established intrinsic brain networks at resting stage including the default mode network (DMN), the anti‐DMN dorsal attention network, and sensorimotor and visual networks .…”
mentioning
confidence: 99%
See 1 more Smart Citation